The effects of student-teacher conferences on English-as-a-foreign-language students' writing performance : - Nguyễn, Thị Ngọc Trang (Can Tho University, 2008)
In the English Department, Cantho University, the technique conferencing has not been widely used. Therefore, this paper aims to explore the effects of student-teacher conferences on our major students' writing performance.